Gender in International Conflict: Women Representation in Security Discourse - Fitriani, Fitriani (Parahyangan Center for International Studies, 2012)
Security discourse that was long cons idered as scientific, objective and gender neutral is one subject that had received numerous feminist critics. It is not only that feminist observed security discourse as minority â including women and victims â blind; it is also masculine and prostatus quo. This article reviews the building of security discourse from feminist perspective that detects, since the theoretical building to the practical level, women are given weak position to justified the strong state. At maximum the rhetoric of women empowerment is used by the state to validate its coercive action.Keywords : international security, genderization, gender studies, feminism